Analisis Penerapan Model Pembelajaran Numbered Head Together Berbantuan Question Card di Sekolah Dasar: Sebuah Kajian Literatur Tahun 2020-2025 - Kadek Budiani; Kadek Hengki Primayana; I Gusti Ngurah Arya Yudaparmita (Alpatih Harapan Semesta, 2026)
The present study aims to explore the application of a Question Card-assisted Numbered Head Together (NHT) teaching model within elementary school settings based on evidence gathered from previous research studies. The research design adopted was a qualitative literature-based review study that involved examining numerous relevant research articles published in the time range from 2020–2025. Data was collected through article searches on the Google Scholar database, and subsequently interpreted through content analysis procedures. The findings obtained from the reviewed studies reveal that the application of the NHT approach combined with Question Card consistently produces a positive impact on learning activity, student motivation, concept understanding, and academic achievement outcomes for elementary school students. This model encourages the involvement of every student in learning through structured group work, while the Question Card acts as a medium that helps focus the discussion and clarify the learning material. Thus, the Question Card-assisted NHT approach can be considered an effective and practical alternative and relevant learning strategy to enhance the effectiveness of teaching and learning activities as well as educational outcomes at the elementary education level.